PRODUCTION AND CHARACTERIZATION OF ALKALINE PROTEASE FROM HALOPHILIC BACTERIA Chromohalobacter japonicus BK-AB18 - Isyana Achmad, Dwi
Proteases are one of the hydrolysis enzymes that cleavage protein into shorter peptide. Proteases represent the largest industrial enzyme that has been applied in various types of industries, such as surfactants/detergents, leather, food, and pharmaceutical industries. These industries require proteases that have a high activity and good performance at various conditions ranging from mild to extreme ones, such as in organic solvent, in detergent and also in the high salinity. Proteases that stable and active in such harsh environment are typically derived from extremophiles microorganisms, which is microorganisms that live in extreme habitat, such as high temperature (thermophiles), low pH (acidophiles) and high salt concentrations (halophiles). The later bacteria are interesting because they can live in hypersaline environment or in other word in a low water activity condition. Extracellular enzymes produces by these bacteria will also have relatively high activity in the solution containing organic solvent or detergent.